2018
DOI: 10.1155/2018/3402983
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Depression Treatment among Older Adults with Parkinson’s Disease and Depression in Ambulatory Care Settings in the United States

Abstract: Little is known regarding depression treatment patterns and predictors among older adults with comorbid Parkinson's disease and depression (dPD) in the United States (US). The objective of this study was to assess the patterns and predictors of depression treatment among older adults with dPD in the US. We adopted a cross-sectional study design by pooling multiple-year data (2005–2011) from the National Ambulatory Medical Care Survey (NAMCS) and the outpatient department of the National Hospital Ambulatory Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Reports of prevalence of depression among PD patients vary greatly throughout the literature, depending on how depressive symptoms or disorders are classified and the study population. In this analysis, 26.46% of the survey sample screened positive for depression, a significant difference compared to 9.94% of those not classified as PD patients (Table 2), consistent with previously reported ranges [2][3][4][5][6]. The prevalence of depression among non-PD patients in our study is similar to the reported prevalence of depression in the general population (8.1%; [28]).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Reports of prevalence of depression among PD patients vary greatly throughout the literature, depending on how depressive symptoms or disorders are classified and the study population. In this analysis, 26.46% of the survey sample screened positive for depression, a significant difference compared to 9.94% of those not classified as PD patients (Table 2), consistent with previously reported ranges [2][3][4][5][6]. The prevalence of depression among non-PD patients in our study is similar to the reported prevalence of depression in the general population (8.1%; [28]).…”
Section: Discussionsupporting
confidence: 91%
“…Parkinson's disease (PD) is a chronic neurodegenerative disease with characteristic motor and non-motor symptoms affecting 572 per 100,000 people aged 45 or older and projected to impact 1,238,000 U.S. individuals by 2030 [1]. Depression is a highly prevalent comorbidity of PD, with prevalence estimates ranging from 22% to 91% [2][3][4] and estimates of concomitant anti-parkinsonian and antidepressant use in older adults ranging from 25% to 58% of patients [5,6], with selective serotonin reuptake inhibitors emerging as the most frequently used antidepressant [5,6]. Moreover, depression is a key predictor of health-related quality of life, with increasing severity corresponding to decreased quality of life [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired neuronal function (14), from neuroinflammation or other causes, is a known driver of depression and related neuropsychiatric problems (511) that often accompany complex CNS disorders, including TBI (12, 13) and CNS disorders with autoimmune components (14), such as multiple sclerosis (MS) (15, 16), Parkinson’s disease (PD) (1719), and Pediatric Acute-onset Neuropsychiatric Syndrome (PANS)/Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS) (20). A recent twin study by Huang, et al, suggests that the causal connection between depression and neuroinflammation may be bidirectional.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results indicate that most nonpharmacological interventions examined in our study had no significant effect on alleviating depressive disorders. This may be due to the use of antidepressant medications and the progression of PD (Schrag et al, 2001;Bhattacharjee et al, 2018;Demarco et al, 2021). Moreover, depression in PD patients is associated with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%